Literatur Review: Kombinasi Aromaterapi Dan Pijat Sebagai Pemicu Produksi ASI - Mega Karina Putri; Andina Vita Sutanto; Yuni Fitriana; Melia Eka Rosita (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2023)
Background: Breastmilk is the best food for babies in their early life. This is because breastmilk has complete nutrients, such as carbohydrates, protein, fat, multivitamins, water, carnitine, and minerals, which babies need. Therefore breastfeeding can guarantee the nutritional status of infants so that child morbidity and mortality decreases. The need for efforts that can be made to help facilitate and increase milk production, such as the use of medicinal plants, oxytocin massage, marmet techniques, acupressure, acupuncture, warm compresses, rolling (back) massage, breast care, and the SPEOS method. Objective: To find out what can be done how to expedite and increase milk production. Methode: This study is a literature review. Sources for conducting this literature review include systematic search studies of computerized databases, namely PubMed and Google Scholar. Result: Increasing prolactin hormone levels can be done in several ways, namely massage, aromatherapy oil compression, and physiological stimulation of the baby while breastfeeding. In addition, massage and breast stimulation can also prevent breast engorgement so that it can maintain the smooth flow of breast milk. In this study it can be concluded that the combination of massage or massage with aromatherapy can increase milk production. The massage techniques used consisted of back massage, oxytocin massage, acupressure, and loving massage. Aromatherapy used in massage includes oil, rose, anise, lime peel, clary sage, lavender, jasmine, and lemongrass. Keywords: production breastmilk, aromatherapy, massage